Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ange.201915140
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Nanoparticles Strain Perovskite Host Lattice Providing Oxygen Capacity and Driving Oxygen Exchange and CH4 Conversion to Syngas

Abstract: Particles dispersed on the surface of oxide supports have enabled a wealth of applications in electro-photo-and heterogeneous catalysis. Dispersing nanoparticles within the bulk of oxides is, however, synthetically much more challenging and therefore less explored, but could open new dimensions to control material properties analogous to substitutional doping of ions in crystal lattices.Here we demonstrate such a concept allowing extensive, controlled growth of metallic nanoparticles, at nanoscale proximity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…In addition, Jalili et al [108] grew a 10-nm-thick LSM film onto (001) STO and (001) LAO substrates using PLD to generate in-plane tensile strain and in-plane compression strain, respectively, and observed a higher tendency for SrO segregation and higher concentrations of surface oxygen vacancies on the tensile strained LSM surface due to the larger spacing available for Sr cation accommodation and the reduced elastic energy on the surface as compared with the bulk. This positive effect of tensile strain on increasing oxygen diffusivity has also been reported on Au dispersed Pr 1.9 Ni 0.71 Cu 0.41 Ga 0.05 O 4+δ [109] and La 0.8 Ce 0.1 Ni 0.4 Ti 0.6 O 3 with embedded metal nanoparticles [110], demonstrating that high concentrations of surface oxygen vacancies can play a key role in accelerating SrO segregation.…”
Section: Strainsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, Jalili et al [108] grew a 10-nm-thick LSM film onto (001) STO and (001) LAO substrates using PLD to generate in-plane tensile strain and in-plane compression strain, respectively, and observed a higher tendency for SrO segregation and higher concentrations of surface oxygen vacancies on the tensile strained LSM surface due to the larger spacing available for Sr cation accommodation and the reduced elastic energy on the surface as compared with the bulk. This positive effect of tensile strain on increasing oxygen diffusivity has also been reported on Au dispersed Pr 1.9 Ni 0.71 Cu 0.41 Ga 0.05 O 4+δ [109] and La 0.8 Ce 0.1 Ni 0.4 Ti 0.6 O 3 with embedded metal nanoparticles [110], demonstrating that high concentrations of surface oxygen vacancies can play a key role in accelerating SrO segregation.…”
Section: Strainsupporting
confidence: 74%
“…The results showed that compressive or tensile interfacial strain can modify the relative concentrations of La and Sr in the interfacial region to achieve better lattice matching. Estrade et al [106,107] also deposited a 20-nm-thick LCM film onto STO (001) and (110) substrates to generate relaxed and tensile strained surfaces, respectively, and their electron energy loss spectroscopy (EELS) results showed that tensile strain can lead to La depletion at the free film surface and La enrichment at the LCM/STO interface, whereas relaxed films were chemically homogeneous. In addition, Jalili et al [108] grew a 10-nm-thick LSM film onto (001) STO and (001) LAO substrates using PLD to generate in-plane tensile strain and in-plane compression strain, respectively, and observed a higher tendency for SrO segregation and higher concentrations of surface oxygen vacancies on the tensile strained LSM surface due to the larger spacing available for Sr cation accommodation and the reduced elastic energy on the surface as compared with the bulk.…”
Section: Strainmentioning
confidence: 99%
“…75–77 Lattice oxygen in the catalyst support dissociates CH 4 in the DRM reaction, leading to the formation of oxygen vacancies. 75,78,79…”
Section: Resultsmentioning
confidence: 99%
“…[75][76][77] Lattice oxygen in the catalyst support dissociates CH 4 in the DRM reaction, leading to the formation of oxygen vacancies. 75,78,79 Consequently, the reaction of CH 4 with lattice oxygen is expected to be an important factor supporting oxygen vacancy formation. Therefore, to investigate the effects of CH 4 on the formation of lattice oxygen defects with or without EF, we took XPS measurements and evaluated the reducibility of CeO 2 .…”
Section: Effects Of Ef On Co 2 Adsorptionmentioning
confidence: 99%
“…135 Furthermore, the thermally induced ex-solution may find merits where the extreme temperature gradient is routine such as in chemical looping combustion or solar thermal applications. [136][137][138] Heterogeneous Doping Reprinted from Kwak et al, 3 with permission, Copyright 2018, Springer Nature.…”
Section: Thermally Induced Ex-solutionmentioning
confidence: 99%